Analysis of financial statements of Thacogroup in NietNam - Mai, Duc Thao (2020)
This research aims at analyzing Thaco Group financial performance over the the last 5 years from 2014 to 2018, in order to assess the corporation’s profitability, liquidity, solvency, asset management, short term and long-term financial position as well as to make recommendations to any red flags identified during the analysis. The quantitative financial analysis flagged up a number of main areas that required further investigation: cash management, return on equity, operating efficiency, inventory management, and accounts receivable. These issues were then further investigated using semi – structured interviews. The red flags raised during the financial analysis were futher explained by the interviewed individuals, who were all senior management at Thaco. Three main recommendations were made for improving business performance of Thaco: (1) more comprehensive information systems for a more decentralized management, (2) less bureaucratic procedures regarding completion of paperwork and processing of requests as well as payments, and (3) the need to reduce and eliminate resistance to change and fear of the unknown.